When Technology Meets Anxiety:The Moderating Role of AI Usage in the Relationship Between Social Anxiety, Learning Adaptability, and Behavioral Problems Among Chinese Primary School Students - Ma G; Tian S; Song Y; Chen Y; Shi H; Li J (Psychology Research and Behavior Management)
GuangYuan Ma,1,* ShiQin Tian,1,* Yang Song,1 Yi Chen,1 Hui Shi,1 JingChi Li2 1School of Humanities and Management Science, Southwest Medical University, Luzhou, 646000, People’s Republic of China; 2Department of Orthopedics, the Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University, Luzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yang Song; Yi Chen, Email fookyuen666@163.com; chenyiswmu@163.comObjective: This study aims to examine the relationships between social anxiety, learning adaptability, AI technology usage, and behavioral problems among primary school students, with a focus on the mediating role of learning adaptability and the moderating role of AI usage.Methods: A cross-sectional survey was conducted among 1240 primary school students aged 8– 15 in Luzhou, Sichuan Province. Social anxiety was measured using the Social Anxiety Scale for Children (SASC), learning adaptability was assessed with the Children’s Learning Adaptability Questionnaire (CSAQ), behavioral problems were evaluated using the Child Behavior Checklist (CBCL), and AI tool usage was gauged through a self-developed questionnaire. Data analysis involved correlation and multiple regression analyses using SPSS, with the moderated mediation effect analyzed through Process Model 59.Results: Social anxiety was found to significantly and positively predict behavioral problems, indicating that higher levels of social anxiety were associated with more behavioral problems. Learning adaptability partially mediated this relationship, suggesting that social anxiety not only directly impacts behavioral problems but also indirectly heightens the risk by reducing learning adaptability. Additionally, AI usage moderated the relationship between learning adaptability and behavioral problems, with a stronger effect of learning adaptability on behavioral problems observed at higher levels of AI usage. Specifically, the positive influence of learning adaptability on behavioral problems became more pronounced as AI usage increased, indicating that frequent AI use can amplify the impact of learning adaptability on behavioral outcomes.Conclusion: Social anxiety increases the risk of behavioral problems in primary school students by diminishing learning adaptability. AI technology plays a moderating role in the relationship between learning adaptability and behavioral problems, with its effects becoming more pronounced at higher levels of AI usage. This highlights the need for educators to focus on improving students’ learning adaptability, judiciously incorporate AI technology, and consider individual differences, particularly mental health, to foster comprehensive and healthy student development.Keywords: social anxiety, learning adaptability, AI usage, behavioral problems, primary school students